Real classrooms, real teachers : the C3 inquiry in practice - Brugar, Kristy A.; Roberts, Kathryn L. (Professor of education) (Teaching and learning social studies., 2021)
"Real Classrooms, Real Teachers: The Inquiry Arc in Practice is aimed at in-service and pre-service teachers, grades 3-8. This text includes six sections: an introduction, one section for each of the four dimensions of the C3 Framework for Social Studies State Standards (National Council for the Social Studies [NCSS], 2013), and a conclusion. Each chapter begins with a vignette based on a real-life social studies lesson authored by a practicing teacher or researcher. This is followed by a sample lesson plan associated with the vignette and suggestions for appropriate texts and supporting materials, as well as suggestions for modifications. As social studies standards shift to place a higher emphasis on critical thinking, inquiry, interaction, and expression, many teachers are scrambling to figure out how to appropriately shift their instruction accordingly. This book provides examples and ideas for working with elementary and middle school students to building the social studies skills and knowledge in order to become independent learners and thinkers. Teaching these skills helps to support students in ways which are important to them, and to society at large"--